Multi-disciplinary trends in artificial intelligence : 10th international workshop, MIWAI 2016, Chiang Mai, Thailand, December 7-9, 2016 : proceedings /: 10th international workshop, MIWAI 2016, Chiang Mai, Thailand, December 7-9, 2016 : proceedings. ([2016]) - Unknown
No abstract available